الحوكمة مقاربة للتنمية في الجزائر دراسة في المضمون وآليات التطبيق في ظل الاستعداد للنشوء والاندماج في الأسواق المالية الدولية - فاطمة الزهراء, رقايقية (Sciences humaines; Vol. 22 (2011): SCIENCES HUMAINES, 2016)
ترتب عن تعثر المسيرة التنموية وعجزها عن تحقيق المتطلبات المجتمعية في معظم الدول النامية وبما فيها الجزائر،  طرح مقاربة جديدة للتنمية من طرف كالات التنمية الدولية تهتم بالجوانب السياسية والمؤسسية،  و ذلك لمسايرة المستجدات والتحولات العالمية على جميع الأصعدة وتعديل الأوضاع الداخلية بمراجعة أدوار مختلف الفاعلين في الدولة (الدولة،  القطاع الخـاص والمجتمع المدني )، إنها الحوكمة كمقاربة سياسية للتنمية بما تتضمنه من مؤشرات ومعايير دولية لقياس نوعيتها .   Resulted from the failure of the development process and its inability to meet the demands of the community in most developing countries, including Algeria, presents a new approach to development by international development agencies that focus on Policy and institutional aspects; to address the evolution and global change at all levels, and change the internal situation to examine the roles of different actors in the state (the state, society and the private sector calendar), is the governance that are considered political approach to development, including indicators and international standards for measuring qualit